2009
DOI: 10.1073/pnas.0905443106
|View full text |Cite
|
Sign up to set email alerts
|

Mapping accessible chromatin regions using Sono-Seq

Abstract: Disruptions in local chromatin structure often indicate features of biological interest such as regulatory regions. We find that sonication of cross-linked chromatin, when combined with a sizeselection step and massively parallel short-read sequencing, can be used as a method (Sono-Seq) to map locations of high chromatin accessibility in promoter regions. Sono-Seq sites frequently correspond to actively transcribed promoter regions, as evidenced by their co-association with RNA Polymerase II ChIP regions, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(178 citation statements)
references
References 27 publications
3
174
1
Order By: Relevance
“…Importantly, DFilter extends seamlessly to optimal integrative analysis of multiple data sets, as we demonstrated by combining DNase-seq and FAIRE-seq data to detect open chromatin. DFilter should also be applicable to other signal detection problems, such as Sono-seq, CLIP-seq and ChIP-exo 1, 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, DFilter extends seamlessly to optimal integrative analysis of multiple data sets, as we demonstrated by combining DNase-seq and FAIRE-seq data to detect open chromatin. DFilter should also be applicable to other signal detection problems, such as Sono-seq, CLIP-seq and ChIP-exo 1, 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The power of deep sequencing enabled by the recent generation of DNA sequencers suggests that variation in the shearing of different chromatin structures will be useful for detecting interesting domains of chromatin structure that will be recognizable by underrepresentation (and perhaps overrepresentation) of regions of the genome in whole-genome sequence reads. Indeed, we and others have recently exploited such impacts on shearing differences to evaluate deep-sequencing strategies for detecting structural features on the chromosomes of yeast and humans (1,59).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the above, to confirm an existence of sequencing dependency on DNA functionality, the Auerbach et al [93] have shown that regions proximal to promoters are prone for sonication breakage, and therefore are the subjects of regional bias. These regions are also responsible for a non-uniform read coverage, producing massive peaks of aligned reads.…”
Section: Platform-specific Biasesmentioning
confidence: 62%